Advances in bioluminescence imaging: new probes from old recipes. (August 2018) - Yao, Zi; Zhang, Brendan S; Prescher, Jennifer A
Highlights: Advances in bioluminescent tool production that mirror trends in fluorescent probe development. New bioluminescent platforms based on naturally occurring luciferases and luciferins. Engineered probes that enable deep tissue and multi-component bioluminescence imaging. Applications of bioluminescent tools to cellular biosensing. Abstract : Bioluminescent probes are powerful tools for visualizing biology in live tissues and whole animals. Recent years have seen a surge in the number of new luciferases, luciferins, and related tools available for bioluminescence imaging. Many were crafted using classic methods of optical probe design and engineering. Here we highlight recent advances in bioluminescent tool discovery and development, along with applications of the probes in cells, tissues, and organisms. Collectively, these tools are improving in vivo imaging capabilities and bolstering new research directions.